2017
DOI: 10.3389/fnhum.2017.00158
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age-Related Macular Degeneration on Postural Sway

Abstract: Purpose: To compare the impact of unilateral vs. bilateral age-related macular degeneration (AMD) on postural sway, and the influence of different visual conditions. The hypothesis of our study was that the impact of AMD will be different between unilateral and bilateral AMD subjects compared to age-matched healthy elderly.Methods: Postural stability was measured with a platform (TechnoConcept®) in 10 elderly unilateral AMD subjects (mean age: 71.1 ± 4.6 years), 10 elderly bilateral AMD subjects (mean age: 70.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Indeed, reports indicate that sensory inputs such as visual, proprioceptive, and vestibular cues are essential to maintaining normal postural control (32). Several studies have shown that postural control changes in tests with subjects who have impaired vision (12, 33, 34), or who have vestibular deficits (22, 35). In our study, we included patients who only have visual deficits (Usher type II), and patients who have both visual and vestibular deficits (Usher type I).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, reports indicate that sensory inputs such as visual, proprioceptive, and vestibular cues are essential to maintaining normal postural control (32). Several studies have shown that postural control changes in tests with subjects who have impaired vision (12, 33, 34), or who have vestibular deficits (22, 35). In our study, we included patients who only have visual deficits (Usher type II), and patients who have both visual and vestibular deficits (Usher type I).…”
Section: Discussionmentioning
confidence: 99%
“…They found that AMD patients were more unstable than the controls in both postural conditions (with or without foam pads), suggesting that elderly subjects may not be able to reweight different sensory inputs to maintain their stability. More recently, Chatard et al (12) studied the impact of AMD on postural sway and observed that AMD subjects were more unstable than controls, again interpreted as being most likely due to the absence of postural adaptive mechanisms which could compensate for their visual deficits.…”
Section: Introductionmentioning
confidence: 99%
“…Chatard et al, studying 10 elderly unilateral AMD subjects, 10 elderly bilateral AMD subjects, and 10 healthy age-matched control subjects, showed that bilateral AMD subjects had a surface area and an antero-posterior displacement of the CoP higher than healthy elderly. Unilateral AMD subjects had more antero-posterior displacement of the CoP than healthy elderly [19]. The authors conclude that because of aging, AMD subjects could have poor postural adaptive mechanisms which increase instability and risk of falls.…”
Section: Age-related Macular Degenerationmentioning
confidence: 84%
“…Our findings were in line with the literature 39 or from previous findings from our group 33 . Several studies showed that the presence of a visual disorders as well as strabismus 40,41 or age-related macular degeneration 42 could affect postural stability. These studies confirmed the importance of visual inputs for reaching body stability.…”
Section: Discussionmentioning
confidence: 99%